Design of GIS-Based Spatial Decision Support System For Hazelnut Cultivation: A Case Study Part of Sakarya, Türkiye - Ustaoglu, Beyza; Sertel, Elif; Kaya, Sinasi; Ezber, Yasemin; Aksoy, Samet; Balik, Hüseyin Irfan; Karakaya, Orhan; Ikiel, Cercis; Koç, Derya Evrim; Beyhan, Neriman (IEEE, 2024)
The objective of this research is to propose an integrated approach to create a Geographic Information System (GIS) based spatial decision support system for sustainable hazelnut agriculture in the process of adaptation to climate change within the scope of a newly started interdisciplinary project. Hazelnut is a temperate climate fruit species. In Turkiye, the Black Sea coastal zone, which has favorable climatic conditions, is naturally a hazelnut growing area and hazelnut is one of the climax plant species. Hazelnut is one of the most important agricultural export products of Turkiye and according to 2023 data, Turkiye is ranked as the first place in the world hazelnut exports with 298.557 tons of hazelnut kernel. Since hazelnut is an economically valuable product and its cultivation is directly dependent on topographical and climatic conditions in large areas, monitoring and planning of hazelnut cultivation under changing climatic conditions is very important for the country's economy. Turkiye is one of the most affected Mediterranean countries due to climate change. The results of temperature, precipitation, and humidity simulations in regional climate models created especially for the Black Sea provide important findings in terms of the necessity for spatial planning based on the ecological requirements of hazelnut. Sustainable and rational use of land, determination of the suitability and quality of land, and integrated evaluation of information such as climate, topography, and soil properties are of great importance and are considered natural resources/heritage for future generations. For this purpose, the province of Sakarya, which is ranked as 3rd in hazelnut production in Turkiye with 82.581 tons, was selected as the study area in this research. In the process of creating the spatial decision support system in the study, many interrelated variables, such as climate, topography, geological conditions, and soil properties, will be evaluated using geostatistical methods and weights obtained from the literature and expert opinion surveys. With the data will be used in the spatial decision support system to be designed with the Analytic Hierarchy Process method approach will be used for the integrated analysis of various geospatial data related to the hazelnut cultivation to determine the most suitable hazelnut cultivation areas and the most appropriate hazelnut cultivars within the scope of adaptation to climate change. We will design a spatial decision support system in the process of climate change adaptation by determining the characteristics of the criteria based on varieties that support rural development in order to ensure sustainable production of hazelnut, which has strategic importance for Turkiye and strengthens competition in the global market.